Implementation facilitators and barriers of person and family-centred emergency care - Mari-Louise Joubert; Neltjie C. van Wyk; Ronell Leech (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: At the time of the research, the nurses in the designated hospital’s emergency department did not implement person- and family-centred care to the detriment of patients and families. They were, however, eager to embark on the implementation of the recommendations of the Registered Nurses Association of Ontario for person- and family-centred care.